2013
DOI: 10.1096/fj.13-233791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyp27A1 gene dosage on atherosclerosis development in ApoE‐knockout mice

Abstract: In humans, sterol 27-hydroxylase (CYP27A1) deficiency leads to cholesterol deposition in tendons and vasculature. Thus, in addition to its role in bile acid synthesis, where it converts cholesterol to 27-hydroxycholesterol (27-OHC), CYP27A1 may also be atheroprotective. Cyp27A1-deficient (Cyp27A1(-/-)) mice were crossed with apolipoprotein E (apoE)-deficient mice. Cyp27A1(+/+)/apoE(-/-) [ApoE-knockout (KO)], Cyp27A1(+/-)/apoE(-/-) heterozygous (het), and Cyp27A1(-/-)/apoE(-/-) [double-knockout (DKO)] mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 33 publications
2
26
0
Order By: Relevance
“…Subsequently, in the setting of hypercholesterolemia (apoe −/− mice), they found that elevation of 27HC by CYP7B1 deletion (apoe −/− ; cyp7b1 −/− mice) or exogenous 27HC administration resulted in increased lipid deposition and greater atherosclerotic lesions [61]. This is consistent with observations from Zurkinden et al that under hypercholesterolemia, complete 27HC inhibition via cyp27a1 deletion (apoe −/− ;cyp27a1 −/− mice) is atheroprotective [62]. …”
Section: The Role Of 27hc In Atherosclerosissupporting
confidence: 78%
See 1 more Smart Citation
“…Subsequently, in the setting of hypercholesterolemia (apoe −/− mice), they found that elevation of 27HC by CYP7B1 deletion (apoe −/− ; cyp7b1 −/− mice) or exogenous 27HC administration resulted in increased lipid deposition and greater atherosclerotic lesions [61]. This is consistent with observations from Zurkinden et al that under hypercholesterolemia, complete 27HC inhibition via cyp27a1 deletion (apoe −/− ;cyp27a1 −/− mice) is atheroprotective [62]. …”
Section: The Role Of 27hc In Atherosclerosissupporting
confidence: 78%
“…In addition, 27HC leads to the activation of the NF-κB pathway through ERα by stimulating Erk1,2 and JNK-dependent IκBα degradation. Conversely, complete 27HC inhibition via cyp27a1 deletion is associated with decreased macrophage infiltration in the aortic root [62]. …”
Section: The Role Of 27hc In Atherosclerosismentioning
confidence: 99%
“…In contrast, 27HC is also important for cholesterol elimination from macrophages, and this works as an atheroprotective effect [13]. Furthermore, in mice CYP27A1 shows gene dose-dependent effect which is likely due to affected reverse cholesterol transport, and atherosclerosis is accelerated in cyp27a1 +/− , but reduced in cyp27a1 −/− mice [51]. As described above, plasma 27HC concentration is strongly correlated with the concentration of cholesterol.…”
Section: Impact Of 27hc On Atherosclerosis and Metabolismmentioning
confidence: 99%
“…Cyp27a1 (+/+) / ApoE (−/−) (ApoE KO), Cyp27a1 (+/−) / ApoE (−/−) (het) and Cyp27a1 (−/−) / ApoE (−/−) (DKO) mice were bred/genotyped as previously published . Mice were maintained under a standard 12 : 12‐h light–dark cycle and fed ad libitum .…”
Section: Methodsmentioning
confidence: 99%
“…To study the athero‐protective role of CYP27A1 in vivo , Cyp27a1 KO mice were crossed with ApoE KO mice known for their propensity to spontaneously develop atherosclerosis, and the resulting offspring were fed a western diet (WD) for 3 and 6 months . The atherosclerosis observed in ApoE KO was abolished in Cyp27a1/ApoE double knockout (DKO) mice.…”
mentioning
confidence: 99%